Pt high-dispersion low-carbon alkane dehydrogenation catalyst as well as preparation method and application thereof

By introducing Sn, Ti, Zn and alkali metal additives into the alumina support and optimizing the preparation process, the stability and carbon deposit problems of low-carbon hydrocarbon dehydrogenation catalysts are solved, and the high reactivity and resistance to carbon deposits of the catalyst are achieved. , which improves the overall performance of the catalyst.

CN119114064AActive Publication Date: 2024-12-13CHAMBROAD CHEM IND RES INST CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202411117245.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-14
Publication Date
2024-12-13
Estimated Expiration
2044-08-14

AI Technical Summary

Technical Problem

The existing low-carbon hydrocarbon dehydrogenation catalysts have problems with low stability, poor repetition of activity and carbon deposits. In particular, the uneven dispersion of Pt active components leads to a degradation of the performance of the catalyst during the reaction.

Method used

By introducing Sn, Ti, Zn and alkali metal additives into the alumina support, controlling the carrier calcining temperature and the pH value of the Pt impregnation liquid, optimizing the catalyst preparation process, forming a stable metal oxide support, and improving the uniform dispersion of Pt and Active particle size enhances the thermal stability and resistance to carbon deposits of the catalyst.

Benefits of technology

It significantly improves the stability and reaction activity of the catalyst, extends the life of the catalyst, reduces the loss of Pt and the carbon deposit rate during the reaction, and improves the conversion and selectivity of low-carbon hydrocarbon dehydrogenation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004993985390000071
    Figure BDA0004993985390000071
  • Figure BDA0004993985390000081
    Figure BDA0004993985390000081
Patent Text Reader

Abstract

The invention belongs to the field of high-performance catalysts, and provides a Pt high-dispersion low-carbon alkane dehydrogenation catalyst and a preparation method and application thereof, Pt active particle size and metal dispersity are cooperatively controlled by controlling a carrier preparation process, Pt impregnation temperature and pH value, catalyst post-treatment and other processes, so that the stability of the catalyst is further improved. After reaction evaluation for 80 hours, the propane conversion rate of the catalyst is only reduced by 3.3%, and the catalyst still has higher reaction stability at the reaction temperature of 630 DEG C. The catalyst has relatively high activity and carbon deposition resistance in the aspect of preparing olefin by dehydrogenation of low-carbon alkane, and the problem of relatively low stability of the existing catalyst is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of high-performance dehydrogenation catalysts and discloses a Pt highly dispersed low-carbon alkane dehydrogenation catalyst and a preparation method and application thereof. Background Art

[0002] The alkane dehydrogenation unit is favored by refining and chemical companies due to its advantages such as short process, low investment, good product quality, high conversion rate, few by-products, and mainly produces low-carbon olefins. Especially after 2020, there will be a blowout development in China. It is expected that by 2025, the production capacity of alkane dehydrogenation units will reach a peak, and the speed of new units will slow down in the later period. According to statistics, by 2023, the production capacity of domestic mobile bed alkane dehydrogenation units that have been put into production and are under construction will reach 20 million tons / year, and the demand for catalysts will be about 3,000 tons / year. However, the domestic demand for catalysts is passive, mainly monopolized by foreign agents, and the price of catalysts is high. Therefore, in the long run, realizing independent research and development and production of catalysts is the only way to solve this problem.

[0003] The application number is CN201910595345.9, and its name is "A platinum-based catalyst for propane dehydrogenation to produce propylene and its preparation method", which discloses a method for preparing a Pt-based propane dehydrogenation catalyst. However, verification found that the catalyst had poor stability and severe carbon deposition during the reaction.

[0004] Patent CN103785384 provides a technology for preparing a low-carbon alkane to olefin catalyst using alumina as a carrier, Sn and alkali metals as additives, and Pt as an active component. The main disadvantage of this catalyst is that the active component Pt is easily dispersed unevenly, resulting in low catalyst stability and activity repeatability, and lacks key technology to ensure uniform dispersion of Pt.

[0005] Combined with existing literature reports, Pt-based low-carbon alkane dehydrogenation catalysts are mainly prepared by impregnation method. However, there are no reports in existing studies on the direct effects of carrier calcination temperature, Pt impregnation solution pH value, impregnation temperature, catalyst post-treatment, etc. on the catalyst Pt active particle size and metal dispersion, as well as the effects on the activity and stability of the catalyst activator. This research is of great significance to the actual industrial dehydrogenation process of the low-carbon alkane dehydrogenation to olefin system. Summary of the invention

[0006] The present invention aims at the many deficiencies in the prior art and provides a Pt highly dispersed low-carbon alkane dehydrogenation catalyst and a preparation method thereof. The Pt active particle size and metal dispersion are coordinated controlled by controlling the carrier preparation process, Pt impregnation temperature and pH value, catalyst post-treatment and other processes, thereby further improving the stability of the catalyst. After 80h reaction evaluation, it was found that the catalyst propane conversion rate was only reduced by 3.3%, and it still had a high reaction stability at a reaction temperature of 630°C. The catalyst has both high activity and anti-carbon deposition ability in the dehydrogenation of low-carbon alkanes to olefins, solving the problem of low stability of existing catalysts.

[0007] The main inventive concepts of the present invention are as follows:

[0008] The inventors found that during the preparation of the alumina carrier, appropriate amounts of Sn, Ti, Zn and alkali metal additives are introduced to make them evenly mixed with the aluminum sol. Through the -HO bond relationship between the metal components, after drying, roasting, dehydration and condensation, with the help of -O- (bridge oxygen bond) connection, a stably combined MOM or MOT (M, T represents Al, Sn, Ti, Zn and alkali metal components) metal oxide carrier is formed. The carrier is dominated by alumina, and the additive metal components are evenly dispersed in the carrier skeleton, which strengthens the interaction between the additive and the carrier, helps to improve the thermal stability and structural stability of the carrier, and at the same time, the alkali metal It is beneficial to neutralize the acidity of the catalyst, slow down the rate of carbon deposition of the catalyst, and improve the reaction stability of the catalyst. At the same time, the dehydrogenation of the additives Sn, Zn, and Ti helps to improve the reaction activity of the catalyst. Secondly, the inventor found in the study that the appropriate impregnation temperature during the impregnation process helps to improve the impregnation depth and uniform dispersion of Pt. In the actual industrial application of the moving bed, it is beneficial to reduce the loss of Pt and extend the life of the catalyst. The pH value of the Pt impregnation solution directly affects the size of the catalyst active particles and the degree of metal dispersion. The larger the active particles, the lower the catalyst metal dispersion, and the worse the corresponding catalyst activity and stability. In addition, the high-temperature roasting and oxychlorination process after impregnation with the Pt solution helps to strengthen the strong -O- (bridge oxygen bond) connection between the carrier, the additive and the Pt, prevent the aggregation of Pt active particles, ensure the uniform dispersion of Pt on the carrier, reduce the loss of Pt during the reaction, and improve the activity and stability of the catalyst.

[0009] Based on the above invention concept, the specific technical solution of this application is as follows:

[0010] A Pt highly dispersed low-carbon alkane dehydrogenation catalyst, wherein the carrier is alumina, Pt is an active component, and the additive is Sn, Ti, Zn or an alkali metal. The contents of the components are as follows based on the total weight of the catalyst: Pt is 0.1-3.0%, Sn is 0.2-3.0%, Ti is 0.1-3.0%, Zn is 0.1-4.0%, alkali metal is 0.5-3.0%, and the balance is the carrier;

[0011] Furthermore, the content of each component is as follows: Pt is preferably 0.2-1.0%, Sn is preferably 0.2-1.0%, Ti is preferably 0.1-1.5%, Zn is preferably 0.5-3.0%, alkali metal is preferably 0.5-2.0%, and the balance is carrier.

[0012] The carrier used is θ-alumina, γ-alumina, α-alumina or a mixture thereof.

[0013] In addition, the inventors also provide a method for preparing the above-mentioned Pt highly dispersed light alkane dehydrogenation catalyst, which specifically comprises the following steps:

[0014] (1) Pseudo-boehmite and metatitanic acid are mixed with water and uniformly mixed, and an appropriate amount of concentrated nitric acid is added at 60-90° C. while stirring, and stirred at the same temperature for 2-5 hours, and then mixed with an aqueous solution containing Sn, Zn, and alkali metal salt precursors, aged at 40-70° C. for 3-8 hours, and then dropped into oil ammonia to form, dried at 120° C., and then calcined at 850-1050° C. for 4-8 hours to obtain a spherical carrier with a particle size of 1.6-1.8 mm for standby use;

[0015] (2) using chloroplatinic acid as a platinum precursor, adding deionized water, hydrochloric acid or ethanolamine to prepare a chloroplatinic acid aqueous solution with a pH value of 1-5 for later use;

[0016] (3) Immerse the support pellets in a chloroplatinic acid aqueous solution, maintain the temperature at 40-65°C for 24 hours, and rotate at 15 r / min. Then, slowly evaporate the water at the same speed and temperature at 65-95°C to completely load Pt on the support.

[0017] (4) The catalyst obtained in step (3) is dried at 120° C., calcined in air containing a small amount of chlorine, then purged with nitrogen to cool, and then reduced with hydrogen to obtain the target catalyst.

[0018] In the above step (1), Sn, Zn and alkali metal salt precursors are all water-soluble; further, the Sn precursor is selected from tin tetrachloride or tin acetate; the alkali metal salt precursor is selected from sodium hydrochloride or sodium nitrate or potassium chloride or potassium nitrate or calcium hydroxide; the Zn precursor is selected from zinc chloride or zinc acetate.

[0019] The amount of the above precursors is determined according to the content of each component based on the total weight of the catalyst: Pt is 0.1-3.0%, Sn is 0.2-3.0%, Ti is 0.1-3.0%, Zn is 0.1-4.0%, and alkali metal is 0.5-3.0%.

[0020] After high-temperature calcination, the carrier is mainly θ-alumina according to the calcination temperature, and can also be a mixture of θ-alumina and one or both of γ-alumina or α-alumina.

[0021] Preferably, in step (1), the mass ratio of pseudo-boehmite, concentrated nitric acid and deionized water used is (9-15):1:(40-60); the mass ratio of Sn, Zn, alkali metal salt precursor and deionized water used is 1:(10-15).

[0022] Preferably, the pH value of the chloroplatinic acid aqueous solution in step (2) is 2-3.

[0023] Preferably, in step (3), the volume ratio of the alumina balls to the chloroplatinic acid aqueous solution is 1:1.2, the immersion temperature is preferably maintained at 50-60°C for 24 hours, the rotation speed is 15r / min, and then the water is slowly evaporated at 70-80°C while the rotation speed remains unchanged.

[0024] Preferably, the drying, calcining and reducing in step (4) are as follows: drying at 120°C for 5-12h, calcining at 450-650°C for 4-8h in air atmosphere, with a space velocity of 600-1200h -1 ; The air contains 0.2-1.0% chlorine by volume. After the roasting is completed, the nitrogen is purged to cool down to 200°C, and then switched to hydrogen for reduction. The hydrogen space velocity is 200-800h -1 , temperature is 400-600℃, holding time is 4-8h.

[0025] The inventors found through experimental comparison that the catalyst prepared by introducing appropriate amounts of Sn, Ti, Zn and alkali metal additives during the preparation of the alumina carrier is more stable than the catalyst obtained by impregnating and loading the additives on the pure alumina carrier. This also further verifies that the carrier preparation technology in this concept helps to strengthen the interaction between the additives and the carrier, and improve the thermal stability and structural stability of the carrier. At the same time, alkali metals are beneficial to neutralize the acidity of the catalyst and slow down the carbon deposition rate of the catalyst. The dehydrogenation effect of Sn, Zn and Ti also helps to improve the reaction activity of the catalyst.

[0026] Controlling the carrier calcination temperature can effectively improve the stability of the catalyst and reduce the occurrence of side reactions. The carrier calcination temperature is 950℃-1000℃, and the carrier crystal phase is mainly θ type. When the carrier calcination temperature is lower than 850℃ or higher than 1050℃, under the same impregnation process, the catalyst conversion rate, selectivity or stability will decrease.

[0027] The inventors further discovered that when the carrier is impregnated with the aqueous solution of chloroplatinic acid, the carrier impregnation temperature and pH value need to be strictly controlled. The carrier impregnation temperature is too low, which can easily lead to uneven Pt impregnation and low metal dispersion. In particular, when the impregnation solution is lower than 45°C, the Pt grains of the active component of the catalyst are generally larger than 4.5nm. The large Pt grains can easily cause the Pt metal dispersion to be lower than 24%, and the catalyst stability is poor during the reaction. The carrier impregnation temperature is too high, which can easily lead to a decrease in carrier strength, affecting the long-term operation of the catalyst. When the pH value of the carrier impregnation solution is too low (pH <1), the acid strength of the catalyst is still high after treatment, resulting in an increase in by-products during the reaction, a decrease in catalyst selectivity, and carbon deposition that seriously affects the stability of the catalyst. When the pH value of the impregnation solution is too high (pH >5), the active component Pt grains are generally larger than 6nm, the Pt in the catalyst is easily unevenly dispersed, and the Pt metal dispersion (<18%) is low, resulting in a rapid decrease in catalyst activity and stability, and the Pt dispersion is still low during the catalyst regeneration process. Therefore, the pH value of the chloroplatinic acid aqueous solution is further optimized to be 2-3.

[0028] At the same time, the inventors discovered through repeated verification that injecting a certain amount of chlorine during the catalyst roasting process not only helps to correct the uneven dispersion problem of the active component Pt that occurs during the impregnation process, but also helps to prevent the re-aggregation of Pt particles during high-temperature roasting of the catalyst, thereby providing a guarantee for the activity and stability of the catalyst. The inventors ultimately determined that the best effect occurs when the air contains 0.2-1.0% by volume of chlorine, thus filling a gap in the field.

[0029] The present invention also discloses a specific application of the above-mentioned low-carbon alkane dehydrogenation catalyst, which is specifically applied in a low-carbon alkane dehydrogenation process, wherein the low-carbon alkane raw material used is propane, isobutane or a mixture of the two, and a fixed bed reactor is used, and the following operations are specifically performed:

[0030] The catalyst was loaded into the constant temperature section of the reactor, purged and dried with nitrogen, and maintained at 200 °C for 4 h. Then the nitrogen was turned off and hydrogen was switched to hydrogen at a space velocity of 100 h. -1 The temperature was raised to 550-630℃ at a rate of 1℃ / min. After the reaction temperature stabilized, low-carbon alkanes were introduced at a mass space velocity of 3-4h -1 , reaction pressure 0-0.1Mpa, hydrogen-to-hydrocarbon molar ratio 0.45, hydrogen sulfide content in hydrogen 100-160ppm.

[0031] The evaluation results show that the catalyst of the present invention has a high alkane conversion rate and reaction stability, and its ability to resist carbon deposition is significantly improved. When propane is used as the raw material, at a reaction temperature of 600°C, the initial propane conversion rate is 39.5%, and the selectivity is 98.3%. After 80 hours of reaction, the propane conversion rate is 36.2%, and the propylene selectivity is 98.6%. The catalyst conversion rate is only reduced by 3.3%. When the reaction temperature is increased to 630°C, within the same reaction time of 80 hours, the propane conversion rate of the catalyst decreases from 42.1% to 30.5%, while the propane conversion rate of the existing commonly used industrial-grade alkane dehydrogenation catalyst decreases from 41.6% to 21.3%. The catalyst exhibits high reaction stability. When isobutane is used as the raw material, at a reaction temperature of 560°C and a reaction time of 80 hours, the isobutane conversion rate decreases from 49.2% to 35.6%, and the isobutene selectivity increases from 92.2% to 93.1%. The isobutane conversion rate of the existing commonly used industrial-grade alkane dehydrogenation catalyst decreases from 45.5% to 25.7%, and the isobutene selectivity increases from 89.6% to 91.5%. It can be seen that the catalyst effect of the present application is significantly better than that of the existing industrial-grade alkane dehydrogenation catalyst.

[0032] In summary, the Pt highly dispersed low-carbon alkane dehydrogenation catalyst provided in the present application has high reaction activity, stability and resistance to carbon deposition, which solves the problems of low stability of existing catalysts, low repetition rate of preparation process, and easy carbon deposition in the reaction process. DETAILED DESCRIPTION

[0033] The present invention is further described below in conjunction with specific examples, but the present invention is not limited to the following examples. The methods are conventional methods unless otherwise specified. In the following examples and experimental examples, all raw materials are commercially available unless otherwise specified. The percentages in the following examples are weight percentages unless otherwise specified. The platinum-containing industrial-grade alkane dehydrogenation catalyst used in the comparative example can be selected from commercial catalysts of UOP or BASF.

[0034] Example 1

[0035] A Pt highly dispersed light alkane dehydrogenation catalyst and a preparation method thereof, the specific steps are as follows:

[0036] (1) Dissolve 0.71 g of tin tetrachloride, 1.86 g of potassium chloride and 3.27 g of zinc acetate in 60 g of deionized water for later use; disperse 80 g of pseudo-boehmite and 1.33 g of metatitanic acid in 320 g of water to obtain pseudo-boehmite slurry, heat and stir evenly at 85°C, add 6.2 g of concentrated nitric acid to the pseudo-boehmite slurry, pour a metal ion aqueous solution containing tin, potassium and zinc into the slurry, continue stirring for 3 h, age at 60°C for 5 h, drop into an oil-ammonia column for molding, dry at 120°C, and calcine at 950°C for 5 h to obtain an alumina carrier with a particle size of 1.6-1.8 mm and containing 0.5% Sn, 1.5% K, 1.0% Ti and 1.5% Zn for later use.

[0037] (2) At 55°C, 30 g of the alumina carrier prepared in step (1) was immersed in 56 ml of a chloroplatinic acid aqueous solution with a pH of 2.5 and a Pt mass fraction of 0.27%. The mixture was immersed at this temperature for 24 h at a rotation speed of 15 r / min. Subsequently, at the same rotation speed, the temperature was raised to 80°C, and excess water was slowly evaporated to remove the catalyst particles until the catalyst particles were distinct. The mixture was then dried at 120°C for 5 h and calcined at high temperature in an air atmosphere with a chlorine content of 0.5% (volume percentage) and an air velocity of 1000 h / min. -1 , calcined at 600℃ for 5h. After calcination, the temperature was cooled to 200℃ under nitrogen purge, and then heated to 550℃ and maintained for 5h under hydrogen atmosphere for catalyst reduction. The hydrogen space velocity was 300h -1 , a light alkane dehydrogenation catalyst containing 0.5% Pt, 0.5% Sn, 1.5% K, 1.0% Ti, and 1.5% Zn was obtained.

[0038] (3) Application of the above-mentioned light alkane dehydrogenation catalyst in propane dehydrogenation, the specific steps are as follows:

[0039] A fixed bed reactor was used. The catalyst was loaded into the constant temperature section of the reactor and dried by nitrogen purge. The temperature was kept at 200 °C for 4 h. Then the nitrogen was turned off and hydrogen was switched. The hydrogen space velocity was 100 h -1 The temperature was raised to 600°C at a heating rate of 1°C / min, propane was used as the raw material, the reaction pressure was normal pressure, the hydrogen-to-hydrocarbon molar ratio was 0.45, and the alkane mass space velocity was 3.5h -1 The dehydrogenation reaction was carried out under the condition that the hydrogen sulfide content in the hydrogen was 120 ppm. The dispersion degree of the catalyst active component Pt metal, the active particle size and the reaction data are shown in Table 1.

[0040] Example 2

[0041] (1) The catalyst was prepared by the method of Example 1;

[0042] (2) Application of low carbon alkane dehydrogenation catalyst in propane dehydrogenation, the specific steps are as follows:

[0043] A fixed bed reactor was used. The catalyst was loaded into the constant temperature section of the reactor and dried by nitrogen purge. The temperature was kept at 200 °C for 4 h. Then the nitrogen was turned off and hydrogen was switched. The hydrogen space velocity was 100 h -1 The temperature was raised to 560°C at a heating rate of 1°C / min, with isobutane as the raw material, the reaction pressure was normal pressure, the hydrogen-to-hydrocarbon molar ratio was 0.45, and the alkane mass space velocity was 3.5h -1 The dehydrogenation reaction was carried out under the condition that the hydrogen sulfide content in the hydrogen was 120 ppm. The dispersion degree of the catalyst active component Pt metal, the active particle size and the reaction data are shown in Table 2.

[0044] Example 3

[0045] The method of Example 1 was used to prepare the catalyst and evaluate its application, except that the carrier calcination temperature was reduced to 800°C, and the other conditions remained unchanged. The raw material was propane, and the dispersion degree of the catalyst active component Pt metal, the active particle size and the reaction data were shown in Table 1.

[0046] Example 4

[0047] The method of Example 1 was used to prepare the catalyst and evaluate its application, except that the carrier calcination temperature was increased to 1100°C, and the other conditions remained unchanged. The raw material was propane, and the dispersion degree of the catalyst active component Pt metal, the active particle size and the reaction data are shown in Table 1.

[0048] Example 5

[0049] The method of Example 1 was used to prepare the catalyst and evaluate its application, except that the carrier impregnation temperature was reduced to 40°C, and the other conditions remained unchanged. The raw material was propane, and the dispersion degree of the catalyst active component Pt metal, the active particle size and the reaction data were shown in Table 1.

[0050] Example 6

[0051] The method of Example 1 was used to prepare the catalyst and evaluate its application, except that the pH value of the impregnation solution of the active component Pt was 1, and the other conditions remained unchanged. The raw material was propane. The metal dispersion degree, active particle size and reaction data of the active component Pt of the catalyst are shown in Table 1.

[0052] Example 7

[0053] The method of Example 1 was used to prepare the catalyst and evaluate its application, except that the pH value of the impregnation solution of the active component Pt was 4, and the other conditions remained unchanged. The raw material was propane. The metal dispersion degree, active particle size and reaction data of the active component Pt of the catalyst are shown in Table 1.

[0054] Example 8

[0055] The method of Example 1 was used to prepare the catalyst and evaluate its application, except that the pH value of the impregnation solution of the active component Pt was 6, and the other conditions remained unchanged. The raw material was propane. The metal dispersion of the active component Pt of the catalyst, the active particle size and the reaction data are shown in Table 1.

[0056] Example 9

[0057] The method of Example 1 was used to prepare the catalyst and evaluate its application, except that no chlorine gas was injected during the air roasting of the catalyst. The dispersion degree of the catalyst active component Pt metal, the active particle size and the reaction data are shown in Table 1.

[0058] Example 10

[0059] The method of Example 1 was used to prepare the catalyst and evaluate its application, except that the reaction temperature was 630° C., the raw material was only propane, and the dispersion degree of the catalyst active component Pt metal, the active particle size and the reaction data are shown in Table 1.

[0060] Comparative Example 1

[0061] The method of Example 1 was used to evaluate the application of the catalyst, except that the catalyst in the fixed bed reactor was selected from existing industrial-grade alkane dehydrogenation catalysts. The dispersion degree of the catalyst active component Pt metal, the active particle size and the reaction data are shown in Table 1.

[0062] Comparative Example 2

[0063] The catalyst application evaluation was carried out using the method of Comparative Example 1, except that the reaction temperature was 630° C., and the dispersion degree of the catalyst active component Pt metal, the active particle size and the reaction data are shown in Table 1.

[0064] Comparative Example 3

[0065] The catalyst application evaluation was carried out using the method of Example 2, except that the catalyst in the fixed bed reactor was selected from existing industrial-grade alkane dehydrogenation catalysts. The dispersion degree of the catalyst active component Pt metal, the active particle size and the reaction data are shown in Table 2.

[0066] The above examples and comparative examples are summarized, and the propane conversion rate and propylene selectivity are compared in the initial 1h and 80h reaction. The effects of the carrier calcination temperature, the impregnation liquid temperature and pH value, and the presence or absence of chlorine during the catalyst calcination process on the active component Pt metal dispersion, catalyst activity, and stability are investigated. The specific results are shown in Table 1.

[0067] Table 1

[0068]

[0069] From the data comparison in Table 1, it can be seen that the alkane dehydrogenation catalyst prepared by the present invention exhibits high catalytic activity and stability in the dehydrogenation reaction of low-carbon alkanes. In Example 1, the propane conversion rate and stability of the dehydrogenation agent are the best.

[0070] By comparing Examples 1, 3, and 4, it is found that a low or high calcination temperature of the carrier will affect the catalyst conversion rate, stability, and Pt metal dispersion. A high calcination temperature may reduce the specific surface area and pore volume, resulting in a lower dispersion of the active component Pt metal.

[0071] By comparing Examples 1 and 5, it is found that the carrier impregnation temperature is too low, which easily leads to low Pt metal dispersion and reduces the catalyst selectivity and stability. In the actual impregnation process, when the impregnation temperature is higher than 70°C, the carrier powder falls off seriously, reducing the catalyst particle strength.

[0072] By comparing Examples 1, 6, 7, and 8, it is found that as the pH value of the carrier impregnation solution increases, the dispersion of the active component Pt metal shows a decreasing trend, the size of the active particles increases, and the propane conversion rate and stability of the catalyst decrease. In actual applications, when the Pt metal dispersion is 28-31% and the active particle size is 3-4 nm, the catalyst performance is optimal.

[0073] By comparing Examples 1 and 9, it was found that the absence of chlorine injection during the catalyst calcination process would lead to a decrease in the dispersion of Pt metal, an increase in the size of active particles, and a decrease in catalyst stability;

[0074] It can be found from Examples 1, 10, Comparative Example 1 and Comparative Example 2 that as the reaction temperature increases, the catalyst conversion rate and selectivity both decrease, but at the same reaction temperature, the catalyst of the present invention has higher reaction activity, selectivity and stability.

[0075] According to the scheme described in Example 2, isobutane was used as the raw material. At the initial 1 h and 80 h of reaction, the isobutane conversion rate and isobutene selectivity of the catalyst of the present invention were compared with those of Comparative Example 3. The specific data are shown in Table 2.

[0076] Table 2

[0077]

[0078] From the comparison of the data in Table 2, it can be found that the catalyst of the present invention has higher catalyst activity and stability than that of Comparative Example 3, and has excellent catalytic effect performance.

[0079] The above is only an embodiment of the present application and does not constitute any form of limitation to the present application. Although the present application is disclosed as above with a preferred embodiment, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A Pt highly dispersed light alkane dehydrogenation catalyst, Features: The carrier is alumina, Pt is an active component, and the additive is Sn, Ti, Zn or an alkali metal. The content of each component based on the total weight of the catalyst is as follows: Pt is 0.1-3.0%, Sn is 0.2-3.0%, Ti is 0.1-3.0%, Zn is 0.1-4.0%, alkali metal is 0.5-3.0%, and the balance is the carrier; The specific steps of its preparation method are as follows: (1) Pseudo-boehmite and metatitanic acid are mixed with water and uniformly mixed, and an appropriate amount of concentrated nitric acid is added at 60-90° C. while stirring, and stirred at the same temperature for 2-5 hours, and then mixed with an aqueous solution containing Sn, Zn, and alkali metal salt precursors, aged at 40-70° C. for 3-8 hours, and then dropped into oil ammonia to form, dried at 120° C., and then calcined at 850-1050° C. for 4-8 hours to obtain a spherical carrier with a particle size of 1.6-1.8 mm for standby use; (2) using chloroplatinic acid as a platinum precursor, adding deionized water, hydrochloric acid or ethanolamine to prepare a chloroplatinic acid aqueous solution with a pH value of 1-5 for later use; (3) Immerse the support pellets in a chloroplatinic acid aqueous solution, maintain the temperature at 40-65°C for 24 hours, and rotate at 15 r / min. Then, slowly evaporate the water at the same speed and temperature at 65-95°C to completely load Pt on the support. (4) The catalyst obtained in step (3) is dried at 120° C., calcined in air containing a small amount of chlorine, then purged with nitrogen to cool, and then reduced with hydrogen to obtain the target catalyst.

2. The catalyst for dehydrogenating light alkanes according to claim 1, Features: The content of each component is as follows: Pt is 0.2-1.0%, Sn is 0.2-1.0%, Ti is 0.1-1.5%, Zn is 0.5-3.0%, alkali metal is 0.5-2.0%, and the balance is carrier.

3. The catalyst for dehydrogenating light alkanes according to claim 1 or 2, Features: The carrier used is θ-alumina, γ-alumina, α-alumina or a mixture thereof.

4. The catalyst for dehydrogenation of light alkanes according to claim 1, Features: In step (1), Sn, Zn and alkali metal salt precursors are all water-soluble; wherein the Sn precursor is selected from tin tetrachloride or tin acetate; the alkali metal salt precursor is selected from sodium hydrochloride or sodium nitrate or potassium chloride or potassium nitrate or calcium hydroxide; and the Zn precursor is selected from zinc chloride or zinc acetate.

5. The light alkane dehydrogenation catalyst according to claim 1, Features: In step (1), the mass ratio of pseudo-boehmite, concentrated nitric acid and deionized water is (9-15):1:(40-60); the mass ratio of Sn, Zn, alkali metal salt precursor and deionized water is 1:(10-15).

6. The catalyst for dehydrogenation of light alkanes according to claim 1, Features: The pH value of the chloroplatinic acid aqueous solution in step (2) is 2-3.

7. The catalyst for dehydrogenation of light alkanes according to claim 1, Features: In step (3), the volume ratio of the alumina balls to the chloroplatinic acid aqueous solution is 1:1.2, and the immersion temperature is maintained at 50-60°C for 24 hours, the rotation speed is 15r / min, and then the water is slowly evaporated at 70-80°C while the rotation speed remains unchanged.

8. The light alkane dehydrogenation catalyst according to claim 1, Features: The drying, calcining and reducing steps in step (4) are as follows: drying at 120°C for 5-12 hours, calcining at 450-650°C for 4-8 hours in an air atmosphere, with a space velocity of 600-1200 h -1 ; The air contains 0.2-1.0% chlorine by volume. After the roasting is completed, the nitrogen is purged to cool down to 200°C, and then switched to hydrogen for reduction. The hydrogen space velocity is 200-800h -1 , temperature is 400-600℃, holding time is 4-8h.

9. The method for preparing the light alkane dehydrogenation catalyst according to claim 1, It is characterized in that The specific steps are as follows: (1) Pseudo-boehmite and metatitanic acid are mixed with water and uniformly mixed, and an appropriate amount of concentrated nitric acid is added at 60-90° C. while stirring, and stirred at the same temperature for 2-5 hours, and then mixed with an aqueous solution containing Sn, Zn, and alkali metal salt precursors, aged at 40-70° C. for 3-8 hours, and then dropped into oil ammonia to form, dried at 120° C., and then calcined at 850-1050° C. for 4-8 hours to obtain a spherical carrier with a particle size of 1.6-1.8 mm for standby use; (2) using chloroplatinic acid as a platinum precursor, adding deionized water, hydrochloric acid or ethanolamine to prepare a chloroplatinic acid aqueous solution with a pH value of 1-5 for later use; (3) Immerse the support pellets in a chloroplatinic acid aqueous solution, maintain the temperature at 40-65°C for 24 hours, and rotate at 15 r / min. Then, slowly evaporate the water at the same speed and temperature at 65-95°C to completely load Pt on the support. (4) The catalyst obtained in step (3) is dried at 120° C., calcined in air containing a small amount of chlorine, then purged with nitrogen to cool, and then reduced with hydrogen to obtain the target catalyst.

10. Use of the low-carbon alkane dehydrogenation catalyst according to claim 1 in an alkane dehydrogenation process, Features: Specifically used in the low-carbon alkane dehydrogenation process, the low-carbon alkane raw material used is propane, isobutane or a mixture of the two, and a fixed bed reactor is used. The specific operations are as follows: The catalyst was loaded into the constant temperature section of the reactor, purged and dried with nitrogen, and maintained at 200 °C for 4 h. Then the nitrogen was turned off and hydrogen was switched to hydrogen at a space velocity of 100 h. -1 The temperature was raised to 550-630℃ at a rate of 1℃ / min. After the reaction temperature stabilized, low-carbon alkanes were introduced at a mass space velocity of 3-4h -1 , reaction pressure 0-0.1Mpa, hydrogen-to-hydrocarbon molar ratio 0.45, hydrogen sulfide content in hydrogen 100-160ppm.

Citation Information

Patent Citations

  • Low carbon alkane dehydrogenation catalyst and preparation method thereof

    CN104107692A

  • Low-carbon alkane dehydrogenation catalyst with highly-dispersed multi-element active components and preparation method of low-carbon alkane dehydrogenation catalyst

    CN108080002A

  • Activated reduction method for low-carbon alkane dehydrogenation catalyst

    CN109382122A

  • Low-carbon alkane dehydrogenation catalyst as well as preparation method and application thereof

    CN113694923A

  • Dehydrogenation catalyst systems and methods of use thereof

    CN115427143A